Ankle Arthroscopy: A Study of Tourniquet Versus No Tourniquet. (May 2014) - Zaidi, Razi; Hasan, Kamrul; Sharma, Aadhar; Cullen, Nicholas; Singh, Dishan; Goldberg, Andrew
Background: More than 10 000 ankle arthroscopy procedures are performed in the United Kingdom annually. Tourniquet use is thought to allow improved visibility and reduce operative time. However this is not without risk as it predisposes to neurovascular injury. The purpose of our study was to establish the feasibility of a subsequent larger randomized controlled trial, to test the hypothesis that tourniquet use might be unnecessary in ankle arthroscopy. Methods: We performed a prospective nonrandomized case control study on 63 patients undergoing ankle arthroscopy to assess the feasibility of a randomized control trial comparing tourniquet versus no tourniquet. All patients had a tourniquet placed on the thigh and a standard arthroscopic technique. In 1 group (n = 31) the tourniquet was routinely inflated, whereas in a second group (n = 32) the tourniquet was not inflated. Demographic data, intraoperative fluid pressures, and visibility were recorded, as were any intraoperative or postoperative complications. Results: There were no significant differences between the 2 groups with respect to duration of operation, maximum intraoperative fluid pressures or visibility, and postoperative complications. In no cases where a tourniquet was not used did the surgeon need to inflate the tourniquet during the case. Conclusion: Most orthopaedic surgeons continue to use a tourniquet routinely for ankle arthroscopy, presumably on the belief that a clear operative view can be achieved only with a tourniquet. The findings of our feasibility study revealed that ankle arthroscopy was possible without the use of a tourniquet. We propose a randomized clinical trial to determine the best option for patient care. Level of Evidence: Level III, comparative series.